An Analytical Study on Equity Research of Stocks in Banking Sector - Thamaraiselvi, R.; Anupama (Indian Journal of Finance, 2008)
The equity market at present is booming, and with the Bull Run in our market and with FII’s pouring money into our market with Industrial expansion and Retail participants increasing, everything seems to be set right for an "EQUITY BOOM" in India. So an individual who wants to earn superior return with substantial amount of risk has to necessarily participate in equity market to get superior returns in the short span of time. Therefore this project is all about guiding those investors who would like to invest in NIFTY 50 with some useful insights about the Banking sector in the Indian market and some company specific information which would help them in selecting their stock and also it would help them in identifying the timing of the purchase, so that one can improve his odd of making money. Hence, the study is an attempt to analyze, the stock price movements based on the fundamental and technical approach in the banking sector over a period of three years and indicate the impact of various factors that affects the stock price. The fundamental analysis basically throws light on the company on a broad scale, its management, its performance over the years, its growth and its future prospects. Through the technical analysis tools like Moving average, MACD and through various trends, it is possible to suggest the short and long term trend of each stock. To conclude, some suggestions can be recommended based on the findings for an easy and profitable investment experience in the current complex investors’ world.